2016
DOI: 10.7771/2157-9288.1120
|View full text |Cite
|
Sign up to set email alerts
|

‘‘Can I drop it this time?’’ Gender and Collaborative Group Dynamics in an Engineering Design-Based Afterschool Program

Abstract: The 21st century has brought an increasing demand for expertise in science, technology, engineering, and math (STEM). Although strides have been made towards increasing gender diversity in several of these disciplines, engineering remains primarily male dominated. In response, the U.S. educational system has attempted to make engineering curriculum more engaging, informative, and welcoming to girls. Specifically, project-based and design-based learning pedagogies promise to make engineering interesting and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
(50 reference statements)
1
22
0
Order By: Relevance
“…For example, in a study of student behaviors in science classrooms, Jovanovic and King () found that boys were significantly more likely to engage in active leadership and manipulation of materials, doing things like directing others, explaining, and manipulating materials; in contrast, girls' participation often focuses on passive assistance and note taking (Jovanovic & King, ; Mewborn, ) or building relationships with others and following directions (Jones et al, ). These patterns result in girls participating to a lesser degree in small group activities (e.g., Hansen, Walker, & Flom, ), while boys actively lead the group (Jovanovic & King, ; Mewborn, ), control the activities and materials (Kahle, Parker, Rennie, & Riley, ; Patrick & Yoon, ), and dominate conversation (Schnittka & Schnittka, ; Smith‐Lovin & Brody, ). Similar findings of male domination of conversation and activity are also seen in undergraduate engineering group activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in a study of student behaviors in science classrooms, Jovanovic and King () found that boys were significantly more likely to engage in active leadership and manipulation of materials, doing things like directing others, explaining, and manipulating materials; in contrast, girls' participation often focuses on passive assistance and note taking (Jovanovic & King, ; Mewborn, ) or building relationships with others and following directions (Jones et al, ). These patterns result in girls participating to a lesser degree in small group activities (e.g., Hansen, Walker, & Flom, ), while boys actively lead the group (Jovanovic & King, ; Mewborn, ), control the activities and materials (Kahle, Parker, Rennie, & Riley, ; Patrick & Yoon, ), and dominate conversation (Schnittka & Schnittka, ; Smith‐Lovin & Brody, ). Similar findings of male domination of conversation and activity are also seen in undergraduate engineering group activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wilson-Lopez et al found that the students' "familial, community, and recreational funds of knowledge" were connected to their understanding and approach to engineering design (p. 278). Schnittka and Schnittka's (2016) study explored "how cultural gender norms are navigated within informal K-12 engineering contexts . .…”
Section: Research Question 3: Impact Of Engineering Design On Studentsmentioning
confidence: 99%
“…Investigations of small group interactions in engineering tend to focus on the undergraduate level [25], [26]. Schnittka and Schnittka [27] explored small group gender dynamics in a design-based afterschool program for middle school students; however, their work was in a rural, primarily White setting, included cooperative group roles within self-selected groups, and has not yet been extended to formal middle school classroom instruction of engineering-based integrated STEM. Compulsory coursework driven by a teacher's need to address specific academic standards in science and associated with grades for students is likely to create a different environment for student interactions than elective, non-graded, informal experiences.…”
Section: Participation In Small Group Engineering Design Activities Amentioning
confidence: 99%
“…In mixed-gender groups of fourth-and fifth-graders, boys were seen to have better ideas and be team leaders [74], often dominating the small group activities and handling of equipment [75], [76]. In addition to boys' control of the physical materials in their small groups, researchers have found that middle school boys also dominated speech in terms of both frequency and volume [27]. This pattern continues into college, when men are more likely to interrupt the women in their small group than they are to interrupt other men [77].…”
Section: Participation In Small Group Engineering Design Activities Amentioning
confidence: 99%